Progressive web app para busca de locais para prática de futebol recreativo - Piantkoski, Willian Jose (2021)
In this project a Progressive Web App was developed using Online to Offline business model, aiming a better user’s experience to schedule soccer matches and find people to play together, based on geolocation using the current web software development technologies. Sports practice is fundamental to human welfare improving health conditions such as a stronger heart, sleep quality and musculature strengthening. Every technology used was chosen to improve the performance and to make the application more accessible to all users. It is possible to conclude that users can find better places to play soccer and companies can manage schedule and places dynamically.